2012
DOI: 10.1103/physreva.86.065801
|View full text |Cite
|
Sign up to set email alerts
|

Quantum optomechanics with a mixture of ultracold atoms

Abstract: We study cavity optomechanics of a mixture of ultracold atoms with tunable nonlinear collisions. We show that atomic collisions provide linear couplings between fictitious condensate oscillators, leading to possibilities of achieving a globally coupled quantum optomechanical network with an integrated atom chip. Potential applications range from simulating collective nonequilibrium dynamics in fields well past physics to probing unique properties of quantum mixtures.PACS numbers: 03.75.Pp, 03.70.+k Recent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…It was also found that the EIT in a three-level atomic ensemble, interacting with a cavity field of an optomechanical system, can be significantly changed by an oscillating mirror [67]. Furthermore, the optomechanical coupling was studied in a system where a singlemode cavity field is coupled to an antiferromagnetic BoseEinstein condensate [68,69], where the mechanical element is provided by spin-wave excitations. It has also been theoretically shown that an optomechanical analogue of EIT can be controlled by a tunable superconducting qubit [70] or a twolevel atom [71,72], which is coupled to a cavity.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that the EIT in a three-level atomic ensemble, interacting with a cavity field of an optomechanical system, can be significantly changed by an oscillating mirror [67]. Furthermore, the optomechanical coupling was studied in a system where a singlemode cavity field is coupled to an antiferromagnetic BoseEinstein condensate [68,69], where the mechanical element is provided by spin-wave excitations. It has also been theoretically shown that an optomechanical analogue of EIT can be controlled by a tunable superconducting qubit [70] or a twolevel atom [71,72], which is coupled to a cavity.…”
Section: Introductionmentioning
confidence: 99%
“…( 40) for the resonant case ω c = ω ex are shown in red-dotted curves, while the energy structures with the numerically exact diagonalization of the Hamiltonian in Eq. (11) for each polariton subspace are shown in black-solid curves. The coincidence between the theoretical method and numerical one shows the validity of GRWA in the regime we are working with.…”
Section: B Eigenenergies and Eigenstatesmentioning
confidence: 99%
“…Various materials are used to construct optomechanical systems in order to increase or control optomechnaical coupling, but the detailed properties of the materials themselves are usually less considered. For example, there are studies that optomechanical systems are coupled to either two-level or other systems via either cavity fields [7][8][9][10][11] or mechanical resonators [12][13][14][15]. However, material properties of cavities and mechanical resonators in these studies are not studied.…”
Section: Introductionmentioning
confidence: 99%
“…The stationary entanglement between mechanical and cavity modes in the * yuxiliu@tsinghua.edu.cn optomechanical systems has been studied [35][36][37][38][39], and such continuous variable entanglement can be used to implement quantum teleportation [40][41][42]. Also both tripartite and bipartite entanglement between mechanical modes and other degrees of freedom can be generated in the optomechanical systems [43][44][45][46][47][48][49] or the hybrid optomechanical systems with an atomic ensemble [50][51][52][53][54][55][56][57][58][59] or a single-atom [60,61] inside the cavity. Moreover, the cavity field mediated entanglement between two macroscopic mechanical resonators in the steady state [62][63][64][65][66][67][68][69][70][71][72] has also been theoretically explored.…”
Section: Introductionmentioning
confidence: 99%